Looking at Differentiated Learning from the Lens of Underachiever Students: Viewpoints, Experiences, and Impacts - Andayani Andayani; Vina Iasha (International Journal Labs, 2023)
This research aimed to comprehensively examine the implementation of differentiated learning strategies for underachiever students—those with untapped potential not commensurate with their academic performance. Employing a descriptive qualitative approach, the study focused on fourth-grade students chosen for their underachieving characteristics. Data collection involved in-depth interviews with the underachieving students, exploring their perspectives on differentiated learning, experiences during the learning process, and the impact on their comprehension of study materials. The analysis revealed valuable insights into the students' opinions regarding the benefits and challenges associated with differentiated learning. It delved into how this approach influenced their understanding of the subject matter, shedding light on the nuanced responses of underachiever students to the application of differentiated learning. The findings from this study offer a profound understanding of how underachiever students perceive and engage with differentiated learning methods. The implications extend to providing educators with crucial insights for designing effective learning strategies tailored to meet the unique needs of underachiever students. By incorporating these insights, educators can enhance academic performance, support the unfolding potential of underachieving students, and contribute to their overall development. This research contributes to the ongoing discourse on improving educational practices for diverse learning needs.